A study on acoustically modulated bunsen flame and its impingement heat transfer. (26th March 2022) - Zhen, H.S.; Liu, H.; Wei, Z.L.; Liu, Z.H.; Liu, X.Y.; Huang, Z.H.
Abstract: This study experimentally examines acoustic-field-flame-interaction by using a low-power loudspeaker to actuate the oscillation of a Bunsen flame. It is observed that under acoustic forcing, the flow dynamics are altered, different patterns of the flame front are triggered, and both flame temperature field and heat transfer characteristics are changed. Moreover, impingement heat transfer is found to be increased when the flame is under acoustic modulation, indicating that acoustics can be used to promote heat transfer for flame impingement heating applications. There is a threshold forcing frequency of 300 Hz, beyond which no interaction between the sound and flame exists. The response of the flame to acoustic excitation exhibits a double-cone structure to naked eyes, and is found to be convectively bubbling, wrinkling and shrinking flame front under high-speed photography. The oscillating flame front height has exactly the same frequency as the sound, but the waveform is non-sinusoidal. Both symmetric and asymmetric distorted flame fronts are observed, with the former occurring at low frequencies while the latter at relatively higher frequencies. The effect of acoustic field on the thermal field is to lower the high-temperature region of the flame. Therefore, the cool core in the centre is narrowed, leading to higher local heat transfer. A ten percent increase in total heat transfer rate is obtained when the optimum nozzle-to-plate distance is coupled with the most effective forcing frequency of 50 Hz. Therefore, acoustic modulation is a feasible technique for promoting heat transfer. Highlights: 1st study on promoting effect of acoustics on Bunsen flame heat transfer. Both amplitude and frequency of the sound changes the shape of flame front. Response of flame front to acoustics is similar to a turbulent one, broadening the space of heat release. Broader space of higher temperature and heat release leads to higher heat transfer rate and efficiency.